PROFIL POSES BERPIKIR KRITIS SISWA DALAM PEMECAHAN MASALAH MATEMATIKA KONTEKSTUAL DITINJAU DARI GAYA KOGNITIF FIELD DEPENDENT-INDEPENDENT DAN GENDER - N, Atik Fitriya; Kusmayadi, Tri Atmojo; Iswahyudi, Gatut (Jurnal Pembelajaran Matematika, 2013)
Abstract: This research was a qualitative descriptive that aims to describe the critical thinking process of male and female senior high school students with dependent and independent cognitive style in solving contextual mathematics problems using Polya steps. Classification of students cognitive styles used group embedded figures test (GEFT). The subjects of this research were 4 students of XI year of SMA Negeri 1 Kartasura selected by purposive sampling. Validity of the data used time triangulation and the technique of data analysis were done by: (1) classifying the data into four problem solving steps: (a) understand the problem, (b) make a plan, (c) carry out the plan, and (d) look back at the completed solution, (2) presenting the data in narrative text, and (3) concluding the thinking process of students in each problem solving steps. The results show as follows: (1) Male students with a field dependent cognitive style in understanding: students are able to organize and analyze information or aspects of a problem. In making a plan: students are able to identify the material that is needed in formulating steps or solutions. In carrying out the plan: students are able in the rational thinking and be able to make a valid conclusions. In looking back: students are able to think rationally. (2) Male students with field independent cognitive styles in understanding: students are able to organize and analyze information or aspect of a problem, capable of conceptualizing, understanding an attitude and thinking rationally. In making a plan: the students were able to identify the material that is needed in formulating steps or solutions. In carrying out the plan: students are able to think rationally, to make a valid conclusions, reflective thinking and understanding an attitude. In looking back: students are able to think reflectively. (3) Female students with a field dependent cognitive style in understanding: students are able to organize and analyze information or aspect of a problem. In making a plan: students are able to identify the material that is needed in formulating steps or solutions. In carrying out the plan: students are able in the rational thinking and be able to make a valid conclusions. In looking back: students are able to think rationally. (4) Female students with field independent cognitive styles in understanding: students are able to organize and analyze information or aspect of a problem, capable of conceptualizing, understanding an attitude and thinking rationally. In making a plan: the students are able to identify the material that is needed in formulating or solutions. In carrying out the plan: students are able to think rationally, to make a valid conclusions, reflective thinking and understanding an attitude. In looking back: students are able to think reflectively and rationally. Keywords: Critical thinking Process, Problem Solving, Cognitive Style, Gender